Potential role of lactylation in intrinsic immune pathways in lung cancer - Huang, Mengdie; Jin, Ye; Zhao, Dandan; Liu, Xingren (Frontiers in Pharmacology, 2025)
Lung cancer, one of the most lethal malignancies, has seen its therapeutic strategies become a focal point of significant scientific attention. Intrinsic immune signaling pathways play crucial roles in anti-tumor immunity but face clinical application challenges despite promising preclinical outcomes. Lactylation, an emerging research focus, may influences lung cancer progression by modulating the functions of histones and non-histone proteins. Recent findings have suggested that lactylation regulates key intrinsic immune molecules, including cGAS-STING, TLR, and RIG-I, thereby impacting interferon expression. However, the precise mechanisms by which lactylation governs intrinsic immune signaling in lung cancer remain unclear. This review presents a comprehensive and systematic analysis of the relationship between lactylation and intrinsic immune signaling pathways in lung cancer and emphasizes the innovative perspective of linking lactylation-mediated epigenetic modifications with immune regulation. By thoroughly examining current research findings, this review uncovers potential regulatory mechanisms and highlights the therapeutic implications of targeting lactylation in lung cancer. Future investigations into the intricate interactions between lactylation and intrinsic immunity are anticipated to unveil novel therapeutic targets and strategies, potentially improving patient survival outcomes.